Long-term outcomes of children with congenital deafness with more than 15 years of cochlear implant experience - Martins, Jorge Humberto (2014)
Objectives: In this study, the authors aim to investigate if cochlear implant (CI) allows the development of oral communication based on audition and if this is a technology that is safe and reliable at a long-term basis.Material and Methods: The participants were divided into two groups: group 1: individuals with 15 or more years of CI experience; group 2: individuals with 10 to 14 years of CI experience. Both groups were evaluated with the tests that compose the evaluation protocol developed in the ENT Service of CHUC – Hospital Geral, described under results.Results: The tonal audiometry results showed statistically significant difference at 250 Hz. The vocal audiometry results showed statistically significant difference at the intensities of 30, 60, 70 and 80 dB SPL. There was no statistically significant difference in the following tests: monosyllables, numbers, sentences, sentences with telephone and vowels. There was statistically significant difference in the following tests: consonants, 100 words, minimal pairs and articulation.Discussion e Conclusion: The results found show that the CI is a safe, reliable and long term efficient rehabilitation technique. The differences found may be related with the progressive reduction of age at implantation, improvements in the technology and progressive increment in speech and language therapy and special education support.